Functional Deficits in the Wrist and Finger Joints of Goalkeepers After 20 Years of Playing Recreational Football - Hilber, Franz; Wiesenberg, Alexander; Kerschbaum, Maximilian; Ernstberger, Antonio; Worlicek, Michael; Nerlich, Michael; Prantl, Lukas; Koch, Matthias; Krutsch, Volker; Krutsch, Werner (Sportverletzung · Sportschaden, 2019)
Background Long-term damage in the hip, knee and ankle joints of football players has been thoroughly discussed in the literature. Compared with outfield players, however, goalkeepers sustain injuries to the upper extremities five times more often. There is a lack of studies on long-term functional damage to the wrist and finger joints of football goalkeepers.Hypothesis Repetitive micro-traumas and injuries lead to degenerative diseases in goalkeepers after 20 years of playing recreational soccer.Methods The personal histories, injury histories and clinical examination findings of the wrist and finger joints of 27 goalkeepers were compared with the findings obtained in a control group of outfield players.Results Goalkeepers were significantly more restricted in finger movement (p < 0.05) and experienced more pain and swelling (p < 0.05) as well as higher levels of instability (p < 0.05) in the wrist and finger joints than outfield players.Conclusion Medical history and clinical findings indicate deficits in the hands of soccer goalkeepers and a high prevalence of joint and ligament injuries sustained to the fingers over the course of their sports activity. This necessitates specific strategies in the future to prevent injuries and long-term posttraumatic deficits.
Keywords: football; goalkeeper; injury; wrist; finger